2006
DOI: 10.1063/1.2171959
|View full text |Cite
|
Sign up to set email alerts
|

Bulk anisotropic composite rare earth magnets

Abstract: Bulk anisotropic composite Nd13.5Fe80Ga0.5B6∕α-Fe and Nd14Fe79.5Ga0.5B6∕Fe–Co magnets with (BH)max=45–50MGOe have been synthesized by blending a Nd–Fe–Ga–B powder with an α-Fe or Fe–Co powder followed by hot compaction at 600–700 °C and hot deformation (die upsetting) at 850–950 °C with a height reduction of 71%. The composite Nd13.5Fe80Ga0.5B6∕α-Fe and Nd14Fe79.5Ga0.5B6∕Fe–Co magnets show microstructures consisting of a very large soft phase up to ∼50μm, which is more than 1000 times larger than the upper siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 4 publications
0
22
1
2
Order By: Relevance
“…The magnets produced from Nd-Fe-B alloys in this way reach a maximum energy product of 50 MGsOe [6], which is lower than the theoretical value. Methods of texturing samarium-cobalt magnets are being studied extensively [7,8], but no favorable results have been obtained so far [9,10].…”
Section: Introductioncontrasting
confidence: 51%
“…The magnets produced from Nd-Fe-B alloys in this way reach a maximum energy product of 50 MGsOe [6], which is lower than the theoretical value. Methods of texturing samarium-cobalt magnets are being studied extensively [7,8], but no favorable results have been obtained so far [9,10].…”
Section: Introductioncontrasting
confidence: 51%
“…When the thickness of exchange-coupled soft inclusions exceeds the critical width of a few nanometers, a small demagnetizing field leads to magnetization reversal in the middle part of the inclusion [2]. Even if this magnetization reversal is reversible (the so-called "exchange spring" behavior) it strongly worsens the performance of the magnet.…”
Section: Numerical Simulation Of Magetostatic Couplingmentioning
confidence: 99%
“…This requirement is set by the short range of magnetic exchange interactions, which are meant to be responsible for the magnetic coupling between the hard and soft magnetic phases. However, recent experiments [1,2] on composite magnets prepared by hot-pressing and hot-deformation of blends of crushed nanocrystalline R 2 Fe 14 B melt-spun ribbons (where R is rare earth) and micron-size iron powders, suggested that the magnetic coupling between the hard and soft phases can also be in much coarser structures. The magnetic coupling in these composite systems is a long-range magnetostatic coupling ensured by a specific layered morphology formed during the hotdeformation process.…”
mentioning
confidence: 99%
“…The hot press and hot deformation method and the two-roller method are extremely demanding, and the process parameters of them cannot be easily controlled [6]. However, if the single-roller method * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%